Field study on nematode resistance in Nelore-breed cattle - Bricarello, P. A.; Zaros, L. G.; Coutinho, L. L.; Rocha, R. A.; Kooyman, F. N. J.; De Vries, E.; Goncalves, J. R. S.; Lima, L. G.; Pires, A. V.; Amarante, A. F. T. (Elsevier B.V., 2007)
The present study evaluated Nelore cattle with different degrees of resistance to natural infections by gastrointestinal nematodes. One hundred weaned male cattle, 11-12 months of age, were kept on the same pasture and evaluated from October 2003 to February 2004. Faecal and blood samples were collected for parasitological, haematological and immunological tests. In February 2004, the 10 most resistant and the 10 most susceptible animals were selected based on individual means of nematode faecal egg counts (FEC). Such animals were slaughtered for worm burden determination and nematode species identification. The repeatability estimates for FEC (+/- S.D.), log-transformed FEC and packed-cell volume (PCV) in all animals were 0.3 (+/- 0.05), 0.26 (+/- 0.04) and 0.42 (+/- 0.05), respectively. The resistant group showed lower FEC and worm burdens than the susceptible group (P < 0.05). There were no significant differences between groups regarding mean body weight, weight gain, PCV and total serum protein values (P > 0.05). The resistant group showed higher total serum IgE levels (P < 0.05) and higher mean eosinophil blood counts. However, the latter was statistically significant only 42 days after the beginning of the study. Nematodes Cooperia punctata and Haemonchus placei were predominant and the correlation between Cooperia and Haemonchus burdens was 0.64 (P < 0.05), which indicated that animals presenting increased numbers of one of those genera probably had increased numbers of the other. The current study provides further evidence of IgE active role in nematode immunity and suggests that total serum IgE level might serve as an additional marker to select Nelore cattle that are responsive to H. placei and C. punctata infections. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cattle; Cooperia; Haemonchus; Oesophagostonium; Nelore breed; IgE; resistance